Precipitation measurements from the Tropical Moored Array: A review and look ahead. (5th November 2018) - Serra, Yolande L.
Abstract : Rainfall is an important component of the global climate system and is one of the essential climate variables (ECVs) highlighted in the implementation plan for the Global Climate Observing System (GCOS). Over 75% of the world's rainfall occurs over open ocean where in situ observations are most sparse. While current satellite algorithms for estimating rainfall have improved considerably over the past few decades, validation of these products using in situ observations remains critical for meeting the requirements of an ECV. This article reviews the current status of continuous, high‐frequency open‐ocean rainfall measurements collected across the tropical Pacific from the Tropical Moored Array (TMA) and outlines upcoming challenges as well as opportunities for these measurements under the Tropical Pacific Observing System (TPOS) 2020 Project now underway. The rainfall observations from the TMA now provide over a 15‐year record at some sites; however, these observations have been drastically reduced in recent years. As the TPOS is reassessed in light of new platforms for observing ocean and atmospheric state variables, this is an opportune time to review the TMA rainfall observations and their important place in the redesign of the TMA as a "full flux" platform, measuring all interfacial fluxes including radiation and rainfall, as well as momentum, latent and sensible heat fluxes. Abstract : Evolution of Tropical Moored Array (TMA) rainfall since 1998 overlaid on HadISST and the 0.2 mm/h contour from the TRMM 3B42 version 7 monthly rainfall product. This article reviews the status of TMA continuous, high‐frequency open‐ocean rainfall measurements collected across the tropical Pacific and outlines upcoming challenges as well as opportunities for these measurements under the Tropical Pacific Observing System (TPOS) 2020 Project.